-3yx+2x+6y-4=0

Simple and best practice solution for -3yx+2x+6y-4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3yx+2x+6y-4=0 equation:


Simplifying
-3yx + 2x + 6y + -4 = 0

Reorder the terms:
-4 + 2x + -3xy + 6y = 0

Solving
-4 + 2x + -3xy + 6y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 2x + -3xy + 4 + 6y = 0 + 4

Reorder the terms:
-4 + 4 + 2x + -3xy + 6y = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 2x + -3xy + 6y = 0 + 4
2x + -3xy + 6y = 0 + 4

Combine like terms: 0 + 4 = 4
2x + -3xy + 6y = 4

Add '-6y' to each side of the equation.
2x + -3xy + 6y + -6y = 4 + -6y

Combine like terms: 6y + -6y = 0
2x + -3xy + 0 = 4 + -6y
2x + -3xy = 4 + -6y

Reorder the terms:
-4 + 2x + -3xy + 6y = 4 + -6y + -4 + 6y

Reorder the terms:
-4 + 2x + -3xy + 6y = 4 + -4 + -6y + 6y

Combine like terms: 4 + -4 = 0
-4 + 2x + -3xy + 6y = 0 + -6y + 6y
-4 + 2x + -3xy + 6y = -6y + 6y

Combine like terms: -6y + 6y = 0
-4 + 2x + -3xy + 6y = 0

The solution to this equation could not be determined.

See similar equations:

| 5x-9=54-4x | | 2x+3y+4x+5x+6x= | | 2x+2x-6=8 | | P+pq-q-p+3pq-3-q+7= | | 6m^2+23m+15=0 | | (-5r-4)(-r-6)= | | (k-1)x^2-2x+2k=0 | | 12/w=3 | | 7y-80=xy-6x | | (4x^5)^2/2X^12 | | 18k+29=11k-11y | | 2x+x-5+100=360 | | 2x+x-5+100=90 | | 8-4x=5x+28 | | 2x+x-5+100=180 | | (2a+3b)-(a-2b)= | | X^2+6xy+10y^2=0 | | 8-4x-m=5x+28 | | X^2+5x-2000=0 | | Y=0.66X+3.68 | | R/4=3 | | y=4a^2-3 | | -5v=30 | | 2(4X+11)=(-3)+3X | | -6=b/4 | | V-12=2 | | -132=11p | | -14-m=-8 | | 4(w+2)=28w | | -7=-15-x | | 19xyz+x-y+3xyz+6+y= | | P/14=10 |

Equations solver categories